2016
DOI: 10.1536/ihj.15-297
|View full text |Cite
|
Sign up to set email alerts
|

Tolvaptan Prolongs Blockage of the Vasopressin Type II Receptor Over 24 Hours in Responders With Stage D Heart Failure

Abstract: SummaryThe urine aquaporin-2 (U-AQP2) level relative to the plasma arginine vasopressin (P-AVP) level is a novel predictor of the responsiveness to the vasopressin type 2 receptor (V2R) antagonist tolvaptan (TLV). However, little has been reported about the concentration-time profile of U-AQP2 after TLV treatment. We evaluated 24 patients with decompensated stage D heart failure (HF) who had received 3.75 mg/day of TLV on a de novo basis for > 7 days to treat congestion refractory to conventional diuretics. Se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 29 publications
(31 reference statements)
1
8
0
Order By: Relevance
“…Although tolvaptan has been shown to induce aquaresis, resulting in an amelioration of hyponatraemia in patients with cirrhosis, congestive heart failure and SIAD , to date no direct in vitro evidence has been provided that tolvaptan impairs AQP2 trafficking and insertion to the plasma membrane in collecting duct principal cells in response to vasopressin thus blunting AQP2‐mediated osmotic water permeability. In this respect, a global analysis of the in vitro effect of tolvaptan on rat collecting duct suspension showed that tolvaptan inhibits vasopressin effect on AQP2 phosphorylation at ser256, ser264 and ser269 while inhibiting ser261 .…”
Section: Discussionmentioning
confidence: 99%
“…Although tolvaptan has been shown to induce aquaresis, resulting in an amelioration of hyponatraemia in patients with cirrhosis, congestive heart failure and SIAD , to date no direct in vitro evidence has been provided that tolvaptan impairs AQP2 trafficking and insertion to the plasma membrane in collecting duct principal cells in response to vasopressin thus blunting AQP2‐mediated osmotic water permeability. In this respect, a global analysis of the in vitro effect of tolvaptan on rat collecting duct suspension showed that tolvaptan inhibits vasopressin effect on AQP2 phosphorylation at ser256, ser264 and ser269 while inhibiting ser261 .…”
Section: Discussionmentioning
confidence: 99%
“…Those studies may have missed a considerable amount of urine AQP2. Currently, methods for disrupting EV membranes have been adopted in several studies involving ELISA for urinary AQP2 measurements [10,15]. The localization of the antibody epitope is not unique to AQP2, but also applies to other AQPs where the antibody epitopes are typically at the C-terminus, which are located inside EVs.…”
Section: Discussionmentioning
confidence: 99%
“…Urine osmolality is invariably decreased after the administration of tolvaptan in patients with HF who respond to tolvaptan, 8) and the depressed osmolality sustains for over 24 hours since blood concentration of tolvaptan is often detectable at the trough, especially in cases with renal dysfunction. 9) Therefore, the level of urine osmolality was not changed by marked aquaresis of tolvaptan, even under the significant existence of glycosuria induced by SGLT2i. In other words, diuretic benefit by SGLT2i cannot be simply attributable to glycosuria but also to ameliorating resistance to other diuretic/aquaretic agents, possibly by way of improving renal congestion.…”
Section: Discussionmentioning
confidence: 89%